2021
DOI: 10.3389/fendo.2021.599306
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal Women With a Diagnosis of Endometriosis Have a Significantly Higher Prevalence of a Diagnosis or Symptoms Suggestive of Restless Leg Syndrome: A Prospective Cross-Sectional Questionnaire Study

Abstract: BackgroundEndometriosis and restless leg syndrome (RLS) are both chronic conditions that can negatively affect a woman’s quality of life. A higher prevalence of RLS is seen in women and particularly in those who are pregnant, suggesting a possible ovarian hormonal influence. Endometriosis is a common (affecting 1 in 10 women) estrogen driven gynecological condition, and the prevalence of RLS in women with symptoms or a diagnosis of endometriosis is unknown.MethodsA prospective, cross-sectional, observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The study found a correlation between the IRLSSG rating scale and the rASRAM endometriosis severity score, supporting the research that was conducted by Tempest and col- leagues [12]. The current study showed that there was a correlation between RLS in women with surgically confirmed endometriosis, which showed a significant positive correlation between the severity of endometriosis and the RLS rating scale that is comparable to the study of Sumbodo et al [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study found a correlation between the IRLSSG rating scale and the rASRAM endometriosis severity score, supporting the research that was conducted by Tempest and col- leagues [12]. The current study showed that there was a correlation between RLS in women with surgically confirmed endometriosis, which showed a significant positive correlation between the severity of endometriosis and the RLS rating scale that is comparable to the study of Sumbodo et al [13].…”
Section: Discussionsupporting
confidence: 91%
“…For example, iron deficiency anemia is a http://doi.org/10.33091/amj.2024.147487.1618 recognized cause of RLS [18]. In addition, evidence suggests that women with endometriosis have a significantly reduced hemoglobin concentration and average cell volume compared to controls of the same age [12]. In this study, most patients were below 30 years old in cases [19].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is perhaps unsurprising that systemic iron levels may be unaltered in women with endometriosis, but it is unusual for such a fundamental question to remain without a satisfactory answer. Systemic iron deficiency shares many clinical manifestations with endometriosis, including headache, dizziness or light-headedness, and symptoms of restless leg syndrome ( Allen et al , 2013 ; Tempest et al , 2021 ). If iron deficiency is confirmed to be prevalent in symptomatic women with endometriosis, iron replacement is a readily available treatment option to alleviate at least some of the symptoms that negatively affect quality of life.…”
Section: Discussionmentioning
confidence: 99%